2006 International Conference on Image Processing 2006
DOI: 10.1109/icip.2006.312909
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Binary Tree-Based Progressive Demosaicking Method for Multispectral Filter Array

Abstract: The technique of multispectral filter array (MSFA) is a multispectral extension of the widely deployed color filter array (CFA), which uses single chip sensors and subsequent interpolation strategies to produce full color images. However, multispectral demosaicking presents unique challenges to traditional CFA demosaicking algorithms which cannot be directly extended to deal with various filter arrays with different numbers of spectral bands or different spatial patterns within each band. In addition, the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Demosaicing exercise on the 5-Band dataset serves more to compare demosaicing algorithms as ground-truth images are available. The authors have already shown their approach using Weighted Guided Filter (WGF) [29] to be better than Binary-Tree Edge Sensing algorithm [25][26][27] therefore we choose not to repeat results for Binary Tree. For this camera, we present results both on rendered images from hyperspectral image databases and also on real RAW images captured with this camera.…”
Section: Neural Network Configurationmentioning
confidence: 99%
“…Demosaicing exercise on the 5-Band dataset serves more to compare demosaicing algorithms as ground-truth images are available. The authors have already shown their approach using Weighted Guided Filter (WGF) [29] to be better than Binary-Tree Edge Sensing algorithm [25][26][27] therefore we choose not to repeat results for Binary Tree. For this camera, we present results both on rendered images from hyperspectral image databases and also on real RAW images captured with this camera.…”
Section: Neural Network Configurationmentioning
confidence: 99%
“…d) The filter arrays were executed in accordance with the binary tree approach proposed by Miao et al, 2 a perfect binary tree to be exact, with two levels and three levels corresponding to 4-band and 8-band arrangements respectively, as indicated in Figure 5; e) Two demosaicking algorithms, bilinear interpolation and Miao et al's binary tree based progressive demosaicking, 3 were implemented and compared with vector median technique;…”
Section: Methodsmentioning
confidence: 99%
“…The first notable work in this regard was conducted by Miao et al 2 who developed a generic binary tree based generation method of MSFA spatial arrangement starting from a chequerboard pattern, and further proposed a generic MSFA demosaicking method following the same binary tree structure. 3 To the best of our knowledge, these are the first systematic attempts at MSFA design and demosaicking. This was recently utilised for the further evaluation of the spatial arrangement of filters by Shrestha et al 4 Among a wide spectrum of algorithms proposed for CFA demosaicking in the last decades, some of them might be able to be adapted to MSFA demosaicking due to the intrinsic properties that CFA and MSFA share.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sustained research effort went into designing multispectral filter array (MSFA) [15] and developing associated demosaicking algorithms [14,1,3,16,17,21,22]. Also widely explored is the influence of filter characteristics on colour/spectrum reproduction [19,9,23,24].…”
Section: Introductionmentioning
confidence: 99%